1969
DOI: 10.1126/science.166.3906.755
|View full text |Cite
|
Sign up to set email alerts
|

Berberine: Complex with DNA

Abstract: A complex of calf-thymus DNA with berberine sediments in the analytical ultracentrifuge. The DNA produced systematic changes in the absorption spectrum of berberine which suggest that single alkaloid molecules bind to DNA. Flow dichroism of purines and pyrimidines and of berberine in the complex with DNA had the same signs and magnitudes. Berberine shifted the thermal strand separation profile of DNA to higher temperatures. Therefore, the alkaloid forms a complex with DNA, probably by intercalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Herbal remedies, such as BBR act via interactions with DNA and RNA, cell cycle arrest, and anti-inflammatory and anti-angiogenesis activities (24). The findings of the current study indicated that BBR may be more active in the inhibition of tumor cell proliferation, although BBR shows minor cytotoxicity against normal cells.…”
Section: Discussionmentioning
confidence: 55%
“…Herbal remedies, such as BBR act via interactions with DNA and RNA, cell cycle arrest, and anti-inflammatory and anti-angiogenesis activities (24). The findings of the current study indicated that BBR may be more active in the inhibition of tumor cell proliferation, although BBR shows minor cytotoxicity against normal cells.…”
Section: Discussionmentioning
confidence: 55%
“…The drug thus appears to have a broad antimicrobial activity (2) and seems to be relatively nontoxic to humans (9,18), even though it and its derivatives intercalate themselves into DNA and phospholipid bilayers (5,13) and inhibit enzymes such as alcohol dehydrogenase and xanthine oxidase (22). These latter activities probably account for the ability of berberine sulfate to inhibit reverse transcriptase activity and thereby to inhibit the replication of certain retroviruses (22).…”
mentioning
confidence: 99%
“…Some studies suggest that berberine may either directly bind duplex DNA by intercalation (27)(28)(29)(30) or inflict DNA damage indirectly by its interaction with topoisomerases I and II (28,(31)(32)(33). Other investigators also showed that berberine at 150 mg/ml was able to induce the rate of sister chromatid exchanges, which reflects homologous recombination repair, by several fold (34).…”
Section: Discussionmentioning
confidence: 99%